Шелеп - Перевощиков Генрих Ксенофонтович (Удмуртия, 2004)
Экземпляры: (20220520) / Инвентарный номер: 33050 / Цена: 120.00 / Сис.шифр: 84(2=664.1Удм) / Авт.знак: П 27 / ГРНТИ: 17 / ББК: 84(2=664.1Удм)